Development and evaluation of a new luciferase immunosorbent assay to detect GII.6 norovirus-specific IgG in different domestic and wild animals - Liang, Zhiyan; Zhang, Minyi; Wang, Yu; Koroma, Mark Momoh; Yu, Jingrong; Zhou, Feiyuan; Jing, Duona; Li, Jiaheng; Tang, Shixing; Chen, Qing; Dai, Ying-Chun (Frontiers in Microbiology, 2023)
Noroviruses (NoVs) are the leading viral pathogens globally causing acute gastroenteritis (AGE) in humans, posing a significant global health threat and economic burden. Recent investigations revealed that human NoVs had been detected in different animals, which raises concerns about whether NoVs are potential zoonotic diseases.This study developed a novel luciferase immunosorbent assay (LISA) to detect GII.6NoV IgG based on the VP1 P protein. The LISA showed high specificity (99.20%) and sensitivity (92.00%), with 4-16 times sensitivity compared with ELISA. NoV-LISA was reproducible with human serum regarding the inter-and intra-assay coefficient of variance values. Potential cross-reactivity was also evaluated using mice serum immunized by other antigens, which showed that NoV-LISA could differentiate GII.6NoV from rotavirus and various genotypes of NoV. Specific GII.6 NoV IgG was widely detected in different domestic and wild animals, including dogs, pigs, bats, rats, and home shrews, with various IgG positive rates ranging from 2.5-74.4%. In conclusion, our newly developed NoV-LISA assay is suitable for NoV specific IgG detection in humans and animals. The wide distribution of IgG antibodies against human NoV indicates potential zoonotic transmission between humans and animals.